Intertexuality and intermediality of modern drama-parabola (based on material by Koki Mitany "The Academy of Laugh") - Можарівська, Ірина Олегівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article deals with the problem of finding the manifestations of intertextual reminisces in the English drama of the Renaissance in the context of contemporary drama parabole consideration. On the basis of the play “Akademy of Laugh” by the famous modern Japanese playwright Koki Mitani  the categories of “intertextuality” and “intermediality”are investigated, namely, the features of the manifestations of these aspects in the light  of modern parabolic drama.  In the process of analyzing the play, the author draws attention to the context of intermedial connections of literature with theatrical art, considers the implementation of the principle of “game in play”, traces the manifistations of intercultural interaction between Eastern and Western culture. The events in the drama take place against a backdrop of complicated historical events – The Japan – China War, when the ideological beliefs of the ruling elite of the monarchy took the vector of the Nazi-fascist trend, and the times of general mobilization didn’t encourage the development of a light entertainment genre. The work contains references to the intertextual elements of the dramatic works of the English playwright William Shakespeare (the tragedies "Romeo and Juliet", "Hamlet" and "Macbeth"). The article raises the issue of communicative model of the work, considers the sphere of characters of drama. The comic interpretation of the play is a juxtaposition of cultures and literary genres. The genre features of the work are investigated. The specifity and minimalism of the structure are noted. The attention is focused on the chronotopic specificity of the parabolic work. The article deals with animal symbols, which are considered in the context of ambivalence and ambiguity. The study postulates the idea that through the visualization of intertextual manifestations the intermediality of the work becomes present, as a result of which there is communication of epochs, authors and thoughts. The context of intermedial connections between literature and theatrical art is demonstrated.  The author applies the concept "the theater in the theather", structures the work minimally through dialogue between the author and the censor. Intermediality acts as  a system of interaction of one kind of art in the works of another and reveals mechanisms of mutual influence of kinds of art in the artistic culture of this or that historical period.